Exploring the Dynamics of Personal, Professional and Interprofessional Ethics - Hannah, Elizabeth F. S.; Jindal-Snape, Divya (Book collections on Project MUSE., 2014)
This interdisciplinary book draws on the perspectives of forty authors from four continents to explore the dynamics of ethical dilemmas using theory, research and practice-based examples.